Investigation into the temperature sensing behavior of Yb3+ sensitized Er3+ doped Y2O3, YAG and LaAlO3 phosphors1. Issue 64 (12th July 2015) - Liu, Guofeng; Fu, Linlin; Gao, Zhiyi; Yang, Xingxing; Fu, Zuoling; Wang, Zhiying; Yang, Yanmin
<x xml:space="preserve">Abstract</x> The sensitivities (S) of Y2O3 (YAG/LaAlO3):Yb3+/Er3+ phosphors increased with increasing average bond covalency and the calculated values were basically in good agreement with our experimental results.